Comparison of 208‐week sequential therapy with telbivudine and entecavir in HBeAg‐positive chronic hepatitis B patients with suboptimal responses to 24 weeks of Peg‐IFNα‐2a therapy: An open‐labelled, randomized, controlled, "real‐life" trial. (29th October 2017) - Luo, X. D.; Chen, X. F.; Zhou, Y.; Chen, X. P.
Summary: The purpose of the study was to compare the efficacy and safety of 208‐week sequential therapy with telbivudine and entecavir in HBeAg‐positive chronic hepatitis B (CHB) patients with suboptimal responses to 24 weeks of Peg‐IFNα‐2a therapy. This was an open‐label, randomized, controlled, "real‐life" trial. HBeAg‐positive CHB patients with serum HBV DNA ≥5.0 lg IU/mL and a < 1 lg IU/mL decline of HBsAg level from baseline who underwent at least 24 weeks of Peg‐IFNα‐2a therapy were included. Enrolled patients were randomized to receive either telbivudine (600 mg/d, n = 95) or entecavir (0.5 mg/d, n = 95) for 208 consecutive weeks. Six patients were lost to follow‐up (4 patients in the telbivudine group and 2 in the entecavir group). Treatment was combined with adefovir when week 24 HBV DNA levels declined to <2 lg IU/mL versus baseline, when viral breakthrough occurred during treatment, or when HBV DNA remained detectable at 52 weeks (HBV DNA ≥500 IU/mL). Responses and safety were assessed after 208 weeks of treatment. There were no significant differences among the baseline characteristics, including age, gender, and ALT, HBV DNA, HBsAg or HBeAg levels. After 208 weeks of treatment, there was no significant difference in the rates of undetectable HBV DNA (HBV DNA<500 IU/mL) between the telbivudine group and the entecavir group (84/91, 92.31% vs 88/93, 94.62%, respectively, P  =   .525). More patients in the telbivudine group than the entecavir group achieved HBeAg clearance (74.73% vs 46.24%, respectively, P  <   .001) and HBeAg seroconversion (64.84% vs 38.71%, respectively, P  <   .001). Univariate analysis ( Enter, a  =   0.05) of both groups showed that telbivudine, male gender and baseline HBeAg levels were significantly correlated with HBeAg seroconversion after 208 weeks of sequential therapy. Cox regression analysis ( Enter, a  =   0.05) of the telbivudine group showed that the HBeAg seroconversion rate at 208 weeks was significantly correlated with gender (male) ( P  =   .006, HR =4.406), baseline HBeAg level ( P  =   .005, HR =0.433) and 24 w‐HBeAg level reduction of more than 0.5 lg IU/ml from baseline ( P  =   .027, HR =0.487). All patients tolerated sequential telbivudine treatment; only slightly elevated creatine kinase levels were observed. Stratification analysis found that patients with baseline HBeAg levels less than 3 lg COI who switched to telbivudine may have had significantly improved HBeAg seroconversion rates. In conclusion, telbivudine promotes HBeAg seroconversion that merits investigation in HBeAg‐positive CHB patients with suboptimal responses to 24 weeks of Peg‐IFNα‐2a therapy. We would suggest that patients with baseline HBeAg levels under 3 lg COI switch to telbivudine to achieve higher HBeAg seroconversion rates and use the early reductions in HBeAg levels (24 weeks) to guide treatment.